PLANNING OF A SOLAR POWER PLANT (PLTS) WITH AN OFF – GRID SYSTEM AT SMP NEGERI 4 SUNGAI TEBELIAN SINTANG DISTRICT - Riovanza, Muhammad (Faculty of Engineering, Universitas Tanjungpura, 2025)
Solar Power Plants (PLTS) are one of the environmentally friendly energy sources that utilize sunlight which at the same time reduces dependence on PLN energy which is not only expensive but also often harms the environment. Although building a solar power plant requires a large investment cost, technical planning such as the location of solar panels, system capacity and integrity to the existing power grid are important to consider. This solar power plant was built on the roof of the school's main building. This solar power plant was built using monocrystalline solar panels with a capacity of 670 Wp as many as 14 units, inverter with a capacity of 5000 Watts as many as 2 units, solar charge controller as many as 1 unit and batteries with a capacity of 400 Ah as many as 15 units. This solar power plant is planned to operate for 25 years with 9,306 Wp of energy generated.